Becoming professional artists in postwar Singapore and Malaya: Developments in art during a time of political transition. (14th September 2015) - Low, Yvonne
Abstract : This article aims to recover the background to the post-Second World War growth of local art activities, art education and the rise of the professional artist on the island of Singapore and peninsular Malaya. It examines how the transitional period spanning the dissolution of British colonialism and the establishment of two independent nations stimulated unique conditions for the development of local art education and created an amateur–professional artist divide. The promotion and support of fine arts and related activities were in tandem with nation-building strategies that sought to construct a common 'Malayan' culture and identity.